1999
DOI: 10.1007/s001980050145
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Weather to the Seasonality of Distal Forearm Fractures: A Population-Based Study in Rochester, Minnesota

Abstract: Distal forearm fractures due to falls were more frequent in the winter (p < 0.0001) among Rochester men and women 35 years of age or older in 1952-89. The winter excess was partially explained by a greater relative risk of distal forearm fractures on days with freezing rain (1.65; 95% CI 1.28-2.13) or snow (1.42; 95% CI 1.17-1.74) among women under 65 years of age and on days with freezing rain (1.63; 95% CI 1.23-2.17) among older women. The greater seasonality of forearm compared with hip fractures is explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 27 publications
6
48
0
1
Order By: Relevance
“…Some studies have considered fractures that occur as a result of any fall from a height of less than a meter, such as after having missed 1 to 3 steps in a staircase, as fragility fractures. [50][51][52][53][54][55] Measurement of height loss is a good clinical indicator of vertebral fracture. 56 Klotzbuecher et al 57 performed a meta-analysis of the risk of future fracture, given the history of prior fracture, and concluded that women with prior fracture had a 2-to 10-fold risk of another fracture, compared with those without fracture.…”
Section: Women At Risk Of Fragility Fracturementioning
confidence: 99%
“…Some studies have considered fractures that occur as a result of any fall from a height of less than a meter, such as after having missed 1 to 3 steps in a staircase, as fragility fractures. [50][51][52][53][54][55] Measurement of height loss is a good clinical indicator of vertebral fracture. 56 Klotzbuecher et al 57 performed a meta-analysis of the risk of future fracture, given the history of prior fracture, and concluded that women with prior fracture had a 2-to 10-fold risk of another fracture, compared with those without fracture.…”
Section: Women At Risk Of Fragility Fracturementioning
confidence: 99%
“…The remaining patients experienced ulna shaft fractures (23 patients), dislocation of 1st metacarpal phalangeal joint (1), ankle fracture (1), scaphoid fractures (3), proximal humeral fractures (2), and radial head fractures (1) or closed fracture of opposite wrist (8).…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of falls and months of occurrence revealed that they were increasingly common during the winter months with peak number of falls in January and a fall during the summer of months. Jacobsen et al 8 Open diaphyseal comminution fractures of the distal radius were found in 52 patients (39.4%). They occur more commonly as you get older with a peak about 60e69 years.…”
Section: Discussionmentioning
confidence: 96%
“…Fragility fracture was defined as a fracture that occurred spontaneously or following a minor trauma, such as a fall from standing height or a height less than a metre, a fall from the sitting position or a fall from laying down on a bed or a reclining deck chair from less than a metre high, a fall after having missed one to three steps in a staircase, after a movement outside of the typical plane of motion or coughing [26][27][28][29][30][31].…”
Section: Setting and Participantsmentioning
confidence: 99%